Development of an Immunogenomic Landscape-Based Prognostic Index of Head and Neck Squamous Cell Carcinoma - Long, Jinhua; Zhang, Shichao; Zeng, Xianlin; Ouyang, Yan; Wang, Yun; Hu, Zuquan; Ye, Yuannong; Wu, Weili; Jin, Feng; Zhou, Shi; Zeng, Zhu (Frontiers in Molecular Biosciences, 2020)
Globally, the incidence rate of head and neck squamous cell carcinoma (HNSCC) is about 11%. About 600000 patients are diagnosed as HNSCC every year, and are ranked as the eighth most common cancers. The occurrence and development of tumors are closely related to the immunological function of the body and sensitivity to treatment schemes as well as prognosis. It is urgent for clinicians to make a systematic study of their immune gene map in order to help the selection of the treatment plan and the analysis of curative effect of HNSCC. Here, the genome data of HNSCC samples were downloaded from The Cancer Genome Atlas (TCGA), 4793 genes differentially expressed in normal and cancer tissues of HNSCC were identified, including 1182 down-regulated and 3611 up-regulated genes (IRGs). From these genes, 400 differentially expressed immune related genes were extracted, including 95 down-regulated genes and 305 up-regulated genes. The prognostic values of IRGs were evaluated by univariate Cox analysis, and identified 236 genes that were significantly related to the overall survival of patients. Then, the signaling pathways which play roles in the prognosis IRGs were investigated by Go and KEGG, and the expression profiles of IRGs and overall survival (OS) in survival in 508 HNSCC patients based on the TCGA dataset were integrated. Potential molecular mechanisms and characteristics of these HNSCC‐specific IRGs were further explored with the help of a new prognostic index based on IRGs was developed by Lasso Cox analysis. A total of 64 hub gene（IRGs associated with prognosis） were markedly associated with clinical outcome of HNSCC patients. KEGG functional enrichment analysis revealed that these genes were actively involved in several pathways, e.g., cytokine‐cytokine receptor interaction, T cell receptor signaling, natural killer cell mediated cytotoxicity and T cell receptor signaling, et al. IRGs-based prognostic signature performed moderately in prognostic predictions. Interestingly, the prognostic index based on IRGs reflected infiltration by several types of immune cells. This data screened several IRGs of clinical significance and revealed drivers of the immune repertoire, demonstrating the importance of a personalized IRG‐based immune signature in the recognition, surveillance and prognosis of HNSCC.